0745 The Pharmacokinetics of FT218, Once Nightly Sodium Oxybate: Food Effect and Bioavailability Compared to Twice Nightly Sodium Oxybate. (27th May 2020) - Thorpy, M; Seiden, D; Grassot, J; Monteith, D; Dubow, J; Corser, B
Abstract: Introduction: Sodium oxybate is an effective treatment for excessive daytime sleepiness and cataplexy in patients with narcolepsy. The FDA approved formulation requires twice-nightly dosing; at bedtime and 2.5 - 4 hours later. FT218 is a controlled-release formulation of sodium oxybate intended for once-nightly dosing, using Avadel's proprietary Micropump™ technology. The objective of this study was to evaluate the relative bioavailability of investigational once-nightly sodium oxybate, FT218, 6 g, compared to commercially available twice-nightly sodium oxybate and the food effect of FT218. Methods: Two crossover, single-dose pharmacokinetic studies were conducted in healthy volunteers. The first, a relative bioavailability study (n=28) was completed comparing FT218 6 g to twice-nightly sodium oxybate 6 g (in two divided doses of 3 g). The second, evaluated the food effect (n=16) of FT218 6g in the Fed vs. Fasted state. Results: FT218 had a lower overall Cmax than twice-nightly sodium oxybate, while AUC was equivalent. C8h level and variability was comparable between FT218 and twice-nightly sodium oxybate. In the Fed, compared to the Fasted state, FT218 had a longer Tmax, lower Cmax and decreased AUC (Cmax 67%, AUC 86%, Tmax 1-hour slower than Fasted values). Adverse Events with FT218 were mostly mild or moderate in severity, non-serious and known AEs associated with sodium oxybate. The safety profiles of FT218 and twice-nightly sodium oxybate at 6 g appeared similar. Conclusion: Once-nightly FT218 at 6 g demonstrated a lower overall Cmax and similar exposure to twice-nightly sodium oxybate, with similar C8h plasma levels and C8h variability. In the Fed state, AUC and Cmax of FT218 was lower than in the Fasted State. FT218 was generally safe and well tolerated and the safety profile appeared comparable to twice-nightly sodium oxybate. Support: This work was supported by Avadel Pharmaceuticals.